Hybrid-PjBL: Learning Outcomes, Creative Thinking Skills, and Learning Motivation of Preservice Teacher - Rahardjanto, Abdulkadir; Husamah, Husamah; Fauzi, Ahmad (International Journal of Instruction, 2019)
Hybrid-PjBL is an innovative learning model relevant to the demands of the twenty-first century scheme. The study on Hybrid-PjBL is still rarely conducted by Indonesian researchers and the studies are still limited to the effect of this model on student's thinking skills and metacognitive awareness. Thus, this study aims to examine the effect of Hybrid-PjBL implementation on learning outcomes, creative thinking skills, and student's learning motivation. This study used quasiexperiment, through Nonrandomized Control Group Pretest-Posttest Design. The population was all the sixth-semester students in the Biology Education Department, University of Muhammadiyah Malang. The study sample involved two classes randomly selected from a total of three classes at this institution, comprising students who took Environmental Knowledge course; each class consisted of fifty students. Learning outcomes test sheets, creative thinking skill notes, and motivation questionnaires were instruments used to collect the data. The data obtained were then analyzed using one-way analysis of covariance with the significance level of 5%. The results showed that the application of Hybrid-PjBL had a significant influence on the achievement of learning outcomes and creative thinking skills. The results of this study indicate that Hybrid-PjBL is an alternative learning, suitable to the demands of the twenty-first century.